The Role of New Public Management in Enhancing Regional Budget Efficiency and Public Service Effectiveness in Gorontalo City - Hasiru, Roy; Panigoro, Meyko (Jurnal Manajemen Pelayanan Publik, 2026)
The application of New Public Management (NPM) principles in local government is seen as a strategic approach to improving budget efficiency and public service performance. Yet implementation at the city level continues to face structural and managerial constraints. This study examined the role of NPM in strengthening regional budget efficiency and service effectiveness in Gorontalo City, while identifying mechanisms that support adaptive, transparent, performance-oriented, and inclusive governance. Using a qualitative descriptive interpretative approach, data were collected through in-depth interviews with structural officials, internal auditors, and community representatives, complemented by document analysis of official reports and budget data. Thematic analysis followed the interactive model of Miles and Huberman. The findings show that NPM contributes to budget efficiency through improved planning, tighter monitoring of budget realization, and the integration of digital financial management systems. Service effectiveness also improved through better inter-agency coordination, Key Performance Indicators, and expanded community involvement in monitoring service delivery. However, NPM outcomes are influenced by human resource capacity, leadership consistency, and an organizational culture that supports transparency and accountability. The study concluded that NPM is an essential instrument for promoting efficient and effective local governance, provided that capacity building, internal supervision, and sustained public participation remain priorities.